From ants to robotic explorers: using biologically inspired robots to map the unknown - Emmons, Megan, author; Maciejewski, Anthony A., author; Chong, Edwin K. P., author (Colorado State University. Libraries, 2017)
Robotic swarms are comprised of simple, individual robots but can collectively accomplish complex tasks through frequent interactions with other robots and the environment. One pertinent objective for swarms is mapping unknown, potentially hazardous environments. We show that the collective or emergent behavior of a swarm observed at one area can be used to infer the presence of obstacles in an unknown environment even when the robots are unable to communicate and have limited sensing capabilities. In the process, we present a general methodology for mapping the discrete, individual robot behaviors to a continuous time model of the emergent behavior.
095 - Megan R Emmons
Modelling emergent swarm behavior in robots for mapping unknown environments
Keywords: robotics; robotic swarms; mapping